Optimal metrics for evaluating reusability in web applications - Abbas ali Rezaee; Mohammad Hadi Zahedi (مدیریت مهندسی و رایانش نرم, 2022)
For each software product essential elements in software engineering includes quality, cost and time. Reusability of components can reduce development time and costs and increase product quality. Components used and tested in the past and, can be used and recommended at present too. Evaluation of software reusability is important as evaluation of other qualitative characteristics, and set of methods and criteria are provided for it. In this paper, the optimal set of evaluation criteria for more effective evaluation of reusability of web-based applications has been extracted and recognized. To achieve the optimal set of criteria, the previous criteria has been checked. Then optimum set of criteria has been selected. In other words, based on the criteria for optimal selection criteria, minimum set of criteria that can be fully cover all aspects of web-based software reusability have been recognized and proposed. The performance evaluation of proposed optimal set of selected criteria with content management system, reusability evaluation for every software module could well be done by the developers and the testing system.